Inhibition of PI3K/Akt signaling suppresses epithelial-to-mesenchymal transition in hepatocellular carcinoma through the Snail/GSK-3/beta-catenin pathway - Lee, Seulki (Clin Mol Hepatol, 2020)
BACKGROUND/AIMS: Patients with advanced hepatocellular carcinoma (HCC) have a poor prognosis due to the lack of effective systemic therapies. Epithelial-to-mesenchymal transition (EMT) is a pivotal event in tumor progression, during which cancer cells acquire invasive properties. In this study, we investigated the effects of phosphatidylinositol 3-kinase (PI3K) inhibitors, including LY294002 and idelalisib, on the EMT features of HCC cells in vitro. METHODS: Human HCC cell lines, including Huh-BAT and HepG2, were used in this study. Cell proliferation was measured by 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl tetrazolium bromide, and cell cycle distributions were evaluated using a flow cytometer by propidium iodide staining. Immunofluorescence staining, quantitative real-time polymerase chain reaction, and immunoblotting were performed to detect EMT-associated changes. RESULTS: PI3K inhibitors suppressed the proliferation and invasion of HCC cells and deregulated the expression of EMT markers, as indicated by increased expression of E-cadherin, an epithelial marker, and decreased expression of N-cadherin, a mesenchymal marker, and Snail, a transcription factor implicated in EMT regulation. Furthermore, LY294002 and idelalisib inhibited the phosphorylation of GSK-3β and induced the nuclear translocation of GSK-3β, which corresponded to the downregulation of Snail and β-catenin expressions in Huh-BAT and HepG2 cells. CONCLUSIONS: The inhibition of PI3K/Akt signaling decreases Snail expression by enhancing the nuclear translocation of GSK-3β, which suppresses EMT in HCC cells, suggesting the potential clinical application of PI3K inhibitors for HCC treatment.